Lifestyle modification in the management of insulin resistance states in overweight/obesity: the role of exercise training. Issue 2 (4th May 2019) - Thaane, Tshidi; Motala, Ayesha A; Mckune, Andrew J
Abstract : Physical inactivity is a major contributor to overweight/obesity and associated disorders including cardiovascular diseases (CVDs), diabetes, and insulin resistance (IR). Intensive lifestyle modification (ILM) is recommended as first-line treatment for obese individuals at risk for IR. Exercise is considered to be a critical component of ILM. This narrative review discusses the role of exercise in the management of IR in overweight/obesity. PubMed and Google Scholar were searched for articles published between January 1990 and January 2019 that examined mechanisms behind the effects of exercise on IR states associated with overweight/obesity. Studies examining and/comparing effects of exercise mode, volume and/intensity on IR were also retrieved. Medical Subject Headings (MeSH) used were 'metabolic diseases' OR 'chronic diseases' AND 'exercise' and their related terms. Text words used in conjunction with the MeSH terms were 'aerobic training/exercise' OR 'resistance training/exercise' OR 'high intensity interval training/exercise', OR 'low volume training/exercise'. Reference lists of retrieved articles were also searched for appropriate studies. Aerobic exercise training (AET) and resistance exercise training (RET) appear to produce comparable effects on obesity-induced IR states. RET, however, appears to be associated with greater improvements in glucose disposal in skeletal muscle, which is usually the primary site for IR. This is partly attributed to greater increases in key proteins involved in the insulin signalling pathway including protein content of glucose transporter 4 (GLUT-4) following RET. A study on individuals with impaired glucose tolerance (IGT) showed that RET improved glucose disposal by 23%, primarily due to a 27% increase in non-oxidative glucose metabolism, suggesting that RET may delay the manifestation of diabetes in patients with IGT. Furthermore, studies reviewed here show that components of exercise including the mode, volume and intensity of exercise training are an integral element in exercise prescription and must be recommended in accordance with the desired outcome.